Missionairies in Collision: Anglicans and Oblates among the Gwich'in, 1861-65 - Mishler, Craig (ARCTIC, 1990)
The history of the first missionary efforts among the Gwich'in Athapaskans (Loucheux) living in northeastern Alaska, the northern Yukon Territory, and the northwestern part of the Northwest Territories is vividly portrayed through the correspondence and journals left by the Anglicans James Hunter, William West Kirkby, and Robert McDonald and by their Roman Catholic rivals, the Oblate priests Henri Grollier and Jean Seguin. On several occasions during the early 1860s, the Anglicans and the Oblates found themselves traveling together and competing one on one for the conversion of the Gwich'in. This resulted in some highly charged and dramatic confrontations. Although the Anglicans and Oblates have since reconciled many of their differences, their early competition produced tremendous confusion and turmoil among the Gwich'in, and it effectively foreshadowed other interdenominational conflicts that continue in the present day.